Solusi Penurunan Suhu Lingkungan di Desa Mandalajaya Melalui Penghijauan dan Edukasi Lingkunan Berbasis Masyarakat - Daswa; Risteruw Leonardo Firmansyah; Albar Fadhillah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2022)
Mandalajaya Village faces the challenge of increasing environmental temperatures influenced by global climate change, minimal green open spaces, and the use of less environmentally friendly building materials. This article discusses various solutions that can be applied to reduce the hot temperature in the village, including reforestation through tree planting, utilization of green roofs and plant walls, use of building materials that have good heat insulation, and implementation of environmentally friendly lifestyles. In addition, education and active community involvement are the main keys in efforts to create a cooler and more sustainable environment. With a holistic and collaborative approach, Mandalajaya Village has the potential to become an example of a rural area that is responsive to climate change and committed to environmental conservation.